2013
DOI: 10.5047/eps.2012.08.002
|View full text |Cite
|
Sign up to set email alerts
|

On the coupling of fast and shear Alfvén wave modes by the ionospheric Hall conductance

Abstract: There are two low frequency, magnetised, cold plasma wave modes that propagate through the Earth's magnetosphere. These are the compressional (fast) and the shear Alfvén modes. The fast mode distributes energy throughout the magnetosphere with the ability to propagate across the magnetic field. Previous studies of coupling between these two modes have often focussed on conditions necessary for mode coupling to occur in the magnetosphere. However, Kato and Tamao (1956) predicted mode coupling would occur for no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 80 publications
0
26
0
Order By: Relevance
“…He showed that as compressional oscillations penetrate deep into the magnetosphere, their amplitude decreases several orders of magnitude. Recently, Waters et al (2013) reported that the Hall conductance in the ionosphere can couple shear Alfvén waves trapped in the Ionospheric Alfvén Resonator (IAR) to fast mode waves that propagate across the ambient magnetic field in an ionospheric waveguide. The coupled equation has not been solved, even in a dipole magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…He showed that as compressional oscillations penetrate deep into the magnetosphere, their amplitude decreases several orders of magnitude. Recently, Waters et al (2013) reported that the Hall conductance in the ionosphere can couple shear Alfvén waves trapped in the Ionospheric Alfvén Resonator (IAR) to fast mode waves that propagate across the ambient magnetic field in an ionospheric waveguide. The coupled equation has not been solved, even in a dipole magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, we used the B Z, GSE magnetospheric component and the H ground component. At high and middle latitudes, their behavior should be comparable because of the 90 • rotation of the polarization axes through the ionosphere (Hughes and Southwood, 1974;Sciffer et al, 2005;Piersanti et al, 2012;Waters et al, 2013). During the entire period of interest, the K-index ranges between 0 and 1 (K being the 3 h long quasilogarithmic local index of geomagnetic activity for this observatory: http://roma2.rm.ingv.it/en/).…”
Section: Magnetospheric and Ground Observations: Emd Approachmentioning
confidence: 99%
“…The fast mode, on the other hand, has a component along the ambient field and energy moves in the direction of the wave vector, which can make any angle with the ambient field. The background nonuniform magnetic field couples the two modes and has been discussed in different magnetic field geometries by different authors [ Lanzerotti and Southwood , ; Leonovich , ; Waters et al , ]. The coupled equation has not been solved in dipole magnetic field geometry.…”
Section: Introductionmentioning
confidence: 99%